Exploration study of the potential of weaving techniques in metal application / Rozita Shamsuddin - Shamsuddin, Rozita (2005)
Weaving is one of Malaysian cultural heritage that facing declining nowadays, but there is room for innovation. It is necessary to explore creative design solutions in order to make this technique sustainable. The exploration of different techniques from different fields will encourage and promote traditional skills and handicrafts into becoming a commercially viable con,cern and to foster its growth from the cottage industry to reach the level of a small-scale industry. It is necessary to create a new invention in order to enhance the weaving technique with a new approach in terms of new material besides pandanus leave, mengkuang leave, bamboo or rattan. The combination of weaving technique with metal will creates an innovative design in metal application in the future. To fulfill this purpose, this research utilized an exploratory research. The exploration weaving technique in metal application was done to get a result of the combination between technique and metal. An observation towards weaving technique aim to understand and learned how the process of the technique was done. A set of Questionnaire used to evaluate consumer's opinion and response on the knowledge about weaving technique on jewellery. Based on the questionnaire outcome the making ofproduct prototyping was begun. The finding of this research is 'Plain Weave', the simplest weave construction and 'Simple Coiling Weave' has a potential weaving technique to be applied on metal like copper or silver. Metal from wire is suitable to be applying using weaving technique compared with metal sheet because it is easy to form. The specific thickness ofwire is the important criteria to make a product from weaving technique. The exploration is successfully fulfilled the aim and objective of this research. The product is a new finding in jewellery making in Malaysia using weaving technique. The outcome of this research is one of the solutions to preserve our cultural heritage with a new invention and design.